2017
DOI: 10.1159/000468523
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Retinal Pigment Epithelium Arising in Conjunction with Late Recurrence and Systemic Metastasis of Retinoblastoma

Abstract: In 1974, an 8-month-old male was diagnosed with bilateral retinoblastoma. His left eye was enucleated, while the right eye was salvaged with a combination of external beam radiotherapy (4,000 cGy total, divided in 20 fractions) and retinal laser treatment. Thirty-nine years later, he developed intraocular recurrence of retinoblastoma with extrascleral spread. Histopathological examination also identified a second distinct malignancy, retinal pigment epithelium adenocarcinoma, arising in continuity with the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…One case of RPE adenocarcinoma was detected on histopathology in an eye enucleated for late recurrence of retinoblastoma (RB; bilateral, the other eye was enucleated) with metastases [28]. The authors postulated that an unsuspected RPE tumour arising from RPE hyperplasia occurred secondary to the focal treatment of RB, or that both tumours arose from reactivation of a common cancer stem cell, or that changes in the microenvironment related to the development of RPE adenocarcinoma permitted the exit from dormancy of an RB cancer stem cell [28]. Fiorentzis et al [29] reported a case of an RPE adenoma imitating a malignant transformed melanocytoma at the optic nerve, 10 years after treatment of a peripheral choroidal melanoma in the same eye.…”
Section: Presenting Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…One case of RPE adenocarcinoma was detected on histopathology in an eye enucleated for late recurrence of retinoblastoma (RB; bilateral, the other eye was enucleated) with metastases [28]. The authors postulated that an unsuspected RPE tumour arising from RPE hyperplasia occurred secondary to the focal treatment of RB, or that both tumours arose from reactivation of a common cancer stem cell, or that changes in the microenvironment related to the development of RPE adenocarcinoma permitted the exit from dormancy of an RB cancer stem cell [28]. Fiorentzis et al [29] reported a case of an RPE adenoma imitating a malignant transformed melanocytoma at the optic nerve, 10 years after treatment of a peripheral choroidal melanoma in the same eye.…”
Section: Presenting Symptomsmentioning
confidence: 99%
“…All these conditions have one common denominator, the abnormal proliferation of the RPE incited by various stimuli. One case of RPE adenocarcinoma was detected on histopathology in an eye enucleated for late recurrence of retinoblastoma (RB; bilateral, the other eye was enucleated) with metastases [28]. The authors postulated that an unsuspected RPE tumour arising from RPE hyperplasia occurred secondary to the focal treatment of RB, or that both tumours arose from reactivation of a common cancer stem cell, or that changes in the microenvironment related to the development of RPE adenocarcinoma permitted the exit from dormancy of an RB cancer stem cell [28].…”
Section: Literature Reviewmentioning
confidence: 99%